Preliminary Findings Of Library Staffs' Preparedness In Bridging The Digital Divide - Shaifuddin, Norshila (Persatuan Pustakawan Malaysia, 2009)
This paper reports on the rural library staffs' preparedness towards bridging the digital divide. It focuses on the knowledge of computer and internet technologies of rural library staff; the present computer and internet services provided in rural libraries; and the staffs' perception in overcoming the issues of digital divide. Data collection was carried out through telephone interviews using a guided questionnaire with twenty six respondents. The interview managed to gather ideas, useful insights and respondents suggestions in overcoming problems faced. The study found that library staff had a positive view towards bridging the digital divide. It is clear that rural library staff play a significant role in bridging the digital divide.